The Impact on the STAD Cooperative Learning Method on Speaking Ability among Young English Language Learners - Ni wayan eka oktaviani; Luh Putu Artini; Ni Luh Putu Sri Adnyani (EDUJAVARE: International Journal of Educational Research, 2026)
This study investigates the implementation of the Student Teams Achievement Division (STAD) cooperative learning method and its influence on young English language learners’ speaking ability in a primary school context. The introduction outlines the persistent challenges faced by students in developing speaking proficiency, including low confidence, limited vocabulary, and teacher-centered instructional practices. Using a qualitative case study design featuring an ex post facto perspective, data were collected through classroom observations, semi-structured interviews with teachers and students, and documentation analysis at SD Bali Kiddy. The results show that STAD fosters a supportive, interactive learning environment that significantly enhances students’ speaking confidence, fluency, vocabulary use, and pronunciation. Heterogeneous grouping enables peer scaffolding, allowing lower-ability learners to benefit from modeling and corrective feedback from their peers. The study also identifies students’ positive emotional responses, including reduced anxiety and increased willingness to participate in oral activities